50 creative training closers - Pike, Bob (Jossey-Bass Pfeiffer San FranciscoUS, 1997)
Selects 50 practical training session closers, each designed to reinforce the skills or content taught. Presents closing activities in which participants review the content / indicate how the new learning can be transferred to the workplace / receive rewards for demonstrating new learning. Presents each closer in a structured format with the following elements: objectives, class length (duration of training period), audience, group size, time, equipment, and process.